EP.TU.870Challenges of Surgical Site Infections (SSIs) and Stoma. (28th October 2021) - Ma, Jennifer; Whitehouse, Pauline; McFall, Malcolm
Abstract: Aims: Surgical site infection (SSI) is a costly health burden and is frequently observed in patients who undergo large bowel surgeries with stoma formation. The use of PICO has been associated with reduced rate of SSI and its use is encouraged by NICE. Method: We identified patients who underwent elective or emergency large bowel surgeries, between 2014-2018, using the local database collected for national SSI surveillance. PICO order forms were cross-referenced with SSI database. Analysed data is presented as percentages, and variable testing is performed using Chi Square test. Results: The overall rate of SSIs was 12.7%. 6.8% of the cohort developed an incisional SSI, while 5.9% developed an organ/space SSI. The presence of stoma had a significant impact in the rate of incisional SSI (10.3% v 4.2%; p  = 0.000179). Amongst all patients with PICO dressing applied, stoma formation was associated with a higher rate of incisional SSI (15.2% vs 6.9%, p  = 0.042). 28.7% patients with stoma formation had PICO applied. The use of PICO in this group of patients was associated with statistically significant improvement in the rate of incisional SSI (4.4% v 8.4%; p = 0.026 ) but not in the rate of organ/ space SSI (2.1% v 4.5%; p  = 0.18). Similar findings were not observed when considering elective and emergency cases separately. Conclusion: The risk of incisional SSIs is high in patients with stoma formation, even in those who had PICO dressing fitted. Tricky fitting of PICO dressing in the presence of stoma could be one hurdle in reducing SSIs.